2020
DOI: 10.5999/aps.2019.00815
|View full text |Cite
|
Sign up to set email alerts
|

Successful local use of heparin calcium for congested fingertip replants

Abstract: Background Conventional methods of external bleeding for congested fingertip replants exhibit notable problems, including uncontrollable bleeding and unpredictable survival of the replant. We have added a local injection of heparin calcium to the routine use of systemic heparinization for inducing external bleeding. We retrospectively examined patients who underwent external bleeding using our method. Methods Local subcutaneous injections of heparin calcium were made in 15 congested replants in addition to sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“… 3 Successful replantation gives the satisfactory results of both function and appearance of the fingertips. Although highly successful rates are reported frequently, 4 in some cases, the sites could progress to necrosis and require reconstructive surgery later. Despite many reports, when the nail matrix is found to be preserved with defects in the bone or nail bed, simply covering the stump with flaps will give the fingertips deformities and shorter finger length, resulting in poor satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“… 3 Successful replantation gives the satisfactory results of both function and appearance of the fingertips. Although highly successful rates are reported frequently, 4 in some cases, the sites could progress to necrosis and require reconstructive surgery later. Despite many reports, when the nail matrix is found to be preserved with defects in the bone or nail bed, simply covering the stump with flaps will give the fingertips deformities and shorter finger length, resulting in poor satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Success rates range between 64% and 100%, but topical anticoagulation may be associated with increased blood transfusion requirement (average four units transfused in approximately 50% of patients), partial necrosis in more proximal fingertip zone injuries, and prolonged hospital stay (7-day average, range 5 to 10 days). 32,37,38 Controlled fingertip bleeding is an alternative to leech therapy. 33 A retrospective review was done to determine the efficacy of a controlled external bleeding protocol (24 fingertip replantations in 22 patients; level IV).…”
Section: Topical Anticoagulation and Controlled Bleedingmentioning
confidence: 99%
“…Success rates range between 64% and 100%, but topical anticoagulation may be associated with increased blood transfusion requirement (average four units transfused in approximately 50% of patients), partial necrosis in more proximal fingertip zone injuries, and prolonged hospital stay (7-day average, range 5 to 10 days). 32,37,38…”
Section: Bleeding Leech Therapy and Topical Anticoagulationmentioning
confidence: 99%
“…In addition to dose, one study found increased survival with progressive weaning of heparin rather than abruptly discontinuing it [40] . While systematic heparinization does not appear to impact success rates, two recent studies have supported digit salvage using local injections of heparin [41] or heparin calcium [42] . Preventing complications with arterial inflow and venous outflow is critical for obvious reasons and also because even if caught early salvage rates remain low [43] .…”
Section: In the Literature: Uncertainty And Disagreementmentioning
confidence: 99%